Mutations in the csgD Promoter Associated with Variations in Curli Expression in Certain Strains of Escherichia coli O157:H7 - Uhlich, Gaylen A. (American Society for Microbiology, 2001)
Single-base-pair csgD promoter mutations in human outbreak Escherichia coli O157:H7 strains ATCC 43894 and ATCC 43895 coincided with differential Congo red dye binding from curli fiber expression. Red phenotype csgD::lacZ promoter fusions had fourfold-greater expression than white promoter fusions. Cloning the red variant csgDEFG operon into white variants induced the red phenotype. Substrate utilization differed between red and white variants.